2004
DOI: 10.1063/1.1668657
|View full text |Cite
|
Sign up to set email alerts
|

Generation of large-scale magnetic flows in turbulent plasma

Abstract: Nonlinear dynamics of the magnetic electron drift mode turbulence is outlined and generation of large-scale magnetic structures in a nonuniform unmagnetized plasma by turbulent Reynolds stress is demonstrated. A two-component turbulent system consisting of magnetic fluctuations and generated secondary flows is considered. The evolution equations for mean magnetic flow generation are obtained by averaging the two-field model equations over fast small scales. It is found, in turn, that the pattern of the flow mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…The right-hand side of (3.3a) vanishes with the assumption that |k| ӷ |q| and for coherent interactions one can approximate T q −k ∼ T −k to leading order [34]. This corresponds to neglecting the noise emitted into the flows by the incoherent coupling of magnetic electron drift modes.…”
Section: Excitation Of Large-scale Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…The right-hand side of (3.3a) vanishes with the assumption that |k| ӷ |q| and for coherent interactions one can approximate T q −k ∼ T −k to leading order [34]. This corresponds to neglecting the noise emitted into the flows by the incoherent coupling of magnetic electron drift modes.…”
Section: Excitation Of Large-scale Flowsmentioning
confidence: 99%
“…Note that in deriving these equations (and in contrast to [34]) we did not assume a potential character of the flow (∇ × E = 0). The right-hand side of (3.3a) vanishes with the assumption that |k| ӷ |q| and for coherent interactions one can approximate T q −k ∼ T −k to leading order [34].…”
Section: Excitation Of Large-scale Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhomogeneity of the plasma is due to a density and a temperature gradient, which serve as an energy source for the magnetic electron drift wave turbulence investigated here. 16 The studied drift modes are lowfrequency motions with a typical time scale in between the inverse ion and electron plasma frequencies, and hence we consider plasma consisting of an unpolarized electron fluid and immobile ions, which play a passive role as a neutralizing background, and the dominant role in dynamics is played by the electrons. Therefore, density perturbations can be neglected, i.e., the electron density n equals its equilibrium value n 0 .…”
Section: Basic Equationsmentioning
confidence: 99%
“…14 In order to study the generation of strong magnetic fields within the mentioned frequency range, the nonlinear theory of magnetic electron drift wave turbulence in an unmagnetized inhomogeneous plasma has been developed recently. 15,16 This theory is a two-field theory, describing the magnetic field and temperature evolution, in contrast to the theory of electrostatic drift wave turbulence. It could be shown that structures very similar to large-scale flows in electrostatic drift wave turbulence can be found, the socalled zonal magnetic fields and magnetic streamers.…”
Section: Introductionmentioning
confidence: 99%